High-reliability underfill adhesive suitable for large-size chip and preparation method of high-reliability underfill adhesive
By introducing autonomous synthesis accelerators and additives into the bottom filler of large-size chips, the formulation is optimized to improve the glass transition temperature and high-temperature modulus, and the problem of solder joint tension and warping stress in large-size chip packages is solved. Achieve high reliability and stable chip packaging effect.
Patent Information
- Application Number
- CN202411527908.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
During the packaging process, large-size chips are easily broken due to the difference in thermal expansion coefficients of substrates, chips and solder joints. Ordinary underfill glue is difficult to resist the warping stress of chips and substrates, affecting reliability.
Adopt independent synthesis accelerators and additives, combined with the formulation optimization design, increase the glass transition temperature (Tg) of the bottom filler, reduce the room temperature/low temperature modulus, and increase the high temperature modulus, thereby balancing the chip, substrate, Bump and bottom filler materials degree of reliability between fatigue.
It realizes high reliability after chip packaging, protects the Bump in large-sized chips from being broken by warping stress, avoids failure modes such as chip cracking and layering, and ensures the smooth passage of the chip module in the high-temperature reliability link.
Smart Images

Figure CN119391344A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to a high-reliability bottom filling adhesive suitable for large-size chips and a preparation method thereof. Background Art
[0002] In chip packaging technology, there are a large number of tiny solder bumps in the bonding layer between the IC chip and the organic substrate. They have poor deformation adaptability and are extremely sensitive to thermal stress, making the chip structure reliability problem more prominent. Using polymer bottom filling to improve the reliability of packaged chips is a new method developed in recent years. This method is economical and easy to implement. During the chip packaging process, the bottom filling material (Underfill) gradually solidifies and forms in the narrow gap between the IC chip and the organic substrate through thermal curing, and protects the connected solder joints. At the same time, it can also effectively reduce the impact load, improve the anti-deformation, anti-humidity, and anti-chemical corrosion properties of the packaged chip, and can greatly improve the fatigue life of the packaged chip, so it has great development potential.
[0003] Due to the differences in the thermal expansion coefficients of the substrate, chip, and solder joint materials, if there is no bottom filler, the substrate or chip will deform under the actual application scenarios or the harsh conditions of reliability testing, which will cause stress pulling on the bump, and there is a high probability that the bump will be pulled off. When the bottom filler is applied, the thermal expansion coefficients between the three will be balanced, and the bump will preferably be protected from being pulled off and damaged. However, when the chip size is large, only ordinary bottom filler is not enough to resist the warping stress of the chip and substrate. At this time, the bottom filler is required to balance and offset the warping stress while changing synchronously with the slight changes of the chip, substrate and bump in the actual application scenarios or strict reliability conditions of the chip components, so as to achieve better reliability performance.
[0004] According to the experience of large-size chip packaging testing, when the chip module undergoes multiple reliability links such as reflow soldering and high-temperature storage, the chip-level bottom filler that has been filled and cured needs to have appropriate post-curing properties. For example, the glass transition temperature is moderately increased, the room temperature modulus is moderately reduced, and the high temperature modulus is moderately increased, so that the same reliability fatigue level can be achieved with the three substrates of chip, substrate, and bump, thereby ensuring that the chip module successfully passes the reliability link involving high temperature. Summary of the invention
[0005] In view of the above technical problems, the purpose of the present invention is to provide a high-reliability bottom filling glue suitable for large-size chips and a preparation method thereof. Through the independently synthesized accelerators and additives in the present invention, combined with the optimized formula design, it is finally possible to increase Tg, reduce the room temperature / low temperature modulus, and increase the high temperature modulus under reliability test conditions, thereby achieving a state of reliability fatigue balance between the chip, substrate, Bump and bottom filling material, thereby improving the reliability of the chip after packaging and ensuring that the chip module smoothly passes the reliability link involving high temperature.
[0006] To achieve the above objectives, the technical solutions adopted are as follows:
[0007] One of the purposes of the present invention is to provide a high-reliability bottom filling glue suitable for large-size flip chips, and the raw materials thereof include, by weight:
[0008] 25-35 parts of bisphenol F epoxy resin, 1-3 parts of bisphenol A epoxy resin, 0.5-2 parts of silicon-modified epoxy resin, 0.5-1.5 parts of black paste, 0.8-1.2 parts of coupling agent, 0.1-0.5 parts of flow aid, 50-55 parts of spherical filler, 10-15 parts of curing agent, 0.2-0.8 parts of accelerator premix and / or 0.5-1 parts of additives for controllable post-curing properties.
[0009] Preferably, the bisphenol F type epoxy resin includes: at least one of 830S, 830CRP of Japan DIC, RE-303S-L of Nippon Kayaku, and DER354 of Dow Chemical; the bisphenol A type epoxy resin includes: at least one of 850-S, 850CRP of Japan DIC, RE-310S of Nippon Kayaku, DER383, and DER332 of Dow Chemical; the silicon-modified epoxy resin includes: at least one of Lepmod ES 3201, ES 3201S, and ES 3202 of Complexing High-tech Materials, HSL-50 of Shanghai Huayi, and YLSE-1500 of Nanjing Yuelai.
[0010] Preferably, the black paste is homemade, because using carbon black alone for coloring easily causes carbon black particles to agglomerate. In the present invention, epoxy resin and carbon black are physically blended, and then three-roller dispersion grinding is performed to form a homogeneous paste. Among them, the carbon black is selected from Cabot M800, and the epoxy resin is a blend of bisphenol A epoxy resin and bisphenol F epoxy resin, the bisphenol A epoxy resin is DER332 of Dow Chemical, and the bisphenol F epoxy resin is DER354 of Dow Chemical. The prepared black paste is named HG-01.
[0011] Preferably, the coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane. More preferably, at least one of KBM-403, KBE-403, KBM-303, KBM-802, KBM-803, KBM-903, and KBE-903 of Shin-Etsu of Japan is selected.
[0012] Preferably, the curing agent is at least one of maleic anhydride, benzoic anhydride, phthalic anhydride, succinic anhydride, 4,4'-diamino-3,3'-diethyldiphenylmethane, diethyltoluenediamine, diaminodiphenyl sulfone, m-aminomethylamine, benzyl diamine trimer, and bisbenzyl amino ether. More preferably, at least one of MHHPA of Jiangsu Yarui Chemical, MCD and AA of Nippon Kayaku, and T-5000 and 5200 of Huntsman.
[0013] Preferably, the flow aid is at least one of AC-1201, AC-1202, AC-1203 of Jiangsu Haian Petrochemical, triphenylphosphine, triphenylphosphine oxide of Shanghai Aladdin, BYK-307, BYK-333 of BYK Chemical.
[0014] Preferably, the spherical filler is at least one of SE6050-STE, SO-E2, SO-E2 / 24C, FE920ASQ, 200SE-E4, SC2500-SQ, SE5050-SEJ, and SE2050-SEJ produced by Japan Admatechs Company.
[0015] Preferably, the raw materials for preparing the accelerator premix include an accelerator.
[0016] Preferably, the preparation method of the accelerator comprises the following steps: 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2-ethyl-4-methylimidazole and ethanol are sequentially added into a reaction container, heated to 50-80°C, stirred for 6-10h, and then vacuum filtered the reaction product, and finally dried in an oven at 80-120°C for 2h to obtain the accelerator;
[0017] The specific reaction is as follows:
[0018]
[0019] Preferably, the molar ratio of 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride to 2-ethyl-4-methylimidazole is 1:1-3, and the ratio of the total moles of 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride and 2-ethyl-4-methylimidazole to the moles of ethanol is 1:1-3.
[0020] Preferably, the preparation method of the accelerator premix comprises the following steps: according to parts by weight, 25-35 parts of bisphenol A epoxy resin and 25-35 parts of alicyclic epoxy resin are mixed and stirred evenly, and then 35-45 parts of accelerator are added, stirred evenly and then ground to obtain the accelerator premix, wherein the bisphenol A epoxy resin used is DER332 of Dow Chemical and the alicyclic epoxy resin used is 2021P of Daicel.
[0021] Preferably, the preparation method of the additive with controllable post-curing performance comprises the following steps: heating 70-80 parts of bisphenol F epoxy resin and 20-30 parts of alicyclic amine curing agent to 40-60° C. by weight, mixing and stirring for 1-4 hours, adding 0.5-1 parts of barbituric acid, and continuing to mix and stir for 1-2 hours to obtain the additive with controllable post-curing performance, wherein the bisphenol F epoxy resin used is DER354 of Dow Chemical and the alicyclic amine curing agent is EC331 of BASF.
[0022] The second object of the present invention is to provide a method for preparing a high-reliability bottom filler suitable for large-size flip chips, comprising the following steps:
[0023] Mix 25-35 parts of bisphenol F epoxy resin, 1-3 parts of bisphenol A epoxy resin, 0.5-2 parts of silicon-modified epoxy resin, 0.5-1.5 parts of black paste, 0.8-1.2 parts of coupling agent and 0.1-0.5 parts of flow aid for 1-4 hours; add 50-55 parts of spherical filler in 2-4 times, and continue to stir at a temperature range of 70-90°C for 6-10 hours; then cool to room temperature, first add 10-15 parts of curing agent, control the temperature at 25-30°C and stir for 0.5-2 hours; then add 0.2-0.8 parts of accelerator premix, control the temperature at 25-30°C and stir for 0.5-2 hours; finally add 0.5-1 part of an additive with controllable post-curing performance, control the temperature at 25-30°C and stir for 0.5-2 hours.
[0024] Preferably, the entire preparation process is carried out under vacuum conditions, and the vacuum degree is not less than -0.08Mpa.
[0025] Compared with the prior art, the beneficial effects of the present invention are: by introducing the accelerator premix prepared by independent synthesis and the additives that can control the post-curing, combined with the corresponding formula design, a high-reliability bottom filler suitable for large-size flip chips is finally obtained. This bottom filler has good toughness, suitable glass transition temperature, modulus, and thermal expansion coefficient. The most important thing is that after multiple reliability processes such as reflow soldering, high temperature and high humidity, high temperature storage, and hot and cold cycles, the corresponding glass transition temperature will increase moderately, the room temperature modulus will decrease moderately, and the high temperature modulus will increase significantly, while improving the interface adhesion after reliability. This series of special performances can offset the internal stress generated during the reliability test as much as possible, prevent chip warping, and balance the different changes in the three materials of chip, substrate, and bump during the reliability test. In particular, it can protect the bump at the corners of this large-size chip from being broken by the warping stress, and avoid the failure modes of large-size chips such as cracking and delamination. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a failure diagram of body cracking that occurred in Comparative Example 1 after 7 reflows in the reliability test;
[0027] Figure 2 This is the failure diagram of corner cracks / interface delamination in the reliability test of Comparative Example 1 after PCT 1000;
[0028] Figure 3 This is a diagram of the corner cracks / interface delamination failure that occurred in comparative example 1 after HTST1000h in the reliability test. DETAILED DESCRIPTION
[0029] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0030] 1. Preparation of accelerator
[0031] 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, 2-ethyl-4-methylimidazole, and ethanol are added to a three-necked flask equipped with a stirring paddle, a thermometer, and a condenser tube in sequence. After heating to 60°C, stir for 8 hours. Then the reaction product is vacuum filtered and finally dried in an oven at 100°C for 2 hours. The dried powdered solid (named CJ-01) is the accelerator required by the present invention. Among them, the molar ratio of the 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride to 2-ethyl-4-methylimidazole is 1:2, and the ratio of the total moles of the 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride and 2-ethyl-4-methylimidazole to the moles of ethanol is 1:2.
[0032] 2. Preparation of accelerator premix
[0033] 30 parts of bisphenol A epoxy resin (DER332 from Dow Chemical) and 30 parts of alicyclic epoxy resin (2021P from Daicel) were mixed and stirred evenly, and then 40 parts of CJ-01 were added. After stirring evenly, the mixture was ground three times with a three-roll grinder to obtain an accelerator premix (named CP-01).
[0034] 3. Preparation of additives with controlled post-curing properties
[0035] 79.5 parts of bisphenol F epoxy resin (DER354 from Dow Chemical) and 29.5 parts of alicyclic amine curing agent (EC331 from BASF) were heated to 50°C, mixed and stirred for 2 hours, and then 1 part of barbituric acid was added, and the mixture was mixed and stirred for another hour. Finally, an additive with controllable post-curing properties (named YP-01) was obtained.
[0036] 4. Preparation of black paste
[0037] 40 parts of bisphenol A epoxy resin and 40 parts of bisphenol F epoxy resin were stirred and mixed for 0.5 hours, and 20 parts of carbon black were added in two portions and mixed and stirred for 1 hour. After three-roll grinding for 3 times, the mixture was stirred for 0.5 hours to obtain the final black paste.
[0038] 5. Preparation of high reliability bottom filler for large size flip chips
[0039] 30 parts of bisphenol F epoxy resin, 2 parts of bisphenol A epoxy resin, 1 part of silicon-modified epoxy resin, 0.5 parts of black paste, 1 part of coupling agent, 0.1 parts of flow aid, mixed and stirred for 1 hour; 52 parts of spherical filler were added in 3 times, and the mixture was stirred for 8 hours at a temperature range of 80°C; then the mixture was cooled to room temperature, 12 parts of curing agent were added first, and the mixture was stirred at 25°C for 0.5 hours; then 0.2 parts of accelerator premix were added, and the mixture was stirred at 25°C for 0.5 hours; finally, 1 part of an additive with controllable post-curing performance was added, and the mixture was stirred at 25°C for 0.5 hours. Finally, the preparation was completed. The entire preparation process was carried out under vacuum conditions, and it was preferred that the vacuum degree was maintained at not less than -0.08Mpa during the entire process.
[0040] The formula of the high-reliability bottom filling glue suitable for large-size flip chips is shown in Table 1.
[0041] Table 1. Examples and comparative examples preparation formula (unit: weight parts)
[0042]
[0043]
[0044] Test results and analysis
[0045] Table 2. Reliability results of typical recipe large-size chips (pass or not)
[0046]
[0047] Table 3. Comparison of main properties of examples and comparative examples
[0048]
[0049]
[0050]
[0051] As shown in the data in Table 2, it can be seen intuitively that Comparative Example 1, because it does not contain the homemade accelerator premix and the additive that can control the post-curing, has the following problems during the reliability test: Figure 1 / 2 / 3, while no similar problems occurred in the corresponding reliability test of Example 5, which is comparable to the reliability test level of competing products. (The reliability tests of the actual Example 5, Comparative Example 1, and Competitive Product X were all conducted on large-size flip chips with a chip size of 20*21mm.) The reason for this problem is that the high-temperature modulus change of the bottom filling glue of Comparative Example 1 before and after the reliability test is relatively low, and there is no synchronized microscopic change with the silicon wafer, substrate, and Bump material after the reliability test. Especially for large-size chips, the reliability failure mode mainly occurs at high temperatures, and the synchronization of such microscopic changes plays an important role at this time.
[0052] As shown in Table 2, Comparative Example 1 is a basic formula. Due to reliability issues, after comparing the performance of competing products and conducting a large number of DOE experiments, a homemade accelerator premix and an additive that can control post-curing were obtained to prepare the formula to achieve the performance of competing products.
[0053] From the comparison of the data of Comparative Example 2 and Comparative Example 1, it can be seen that if only the main raw material EC331 in the controllable post-curing additive is used to prepare the formula, although the high-temperature modulus before and after reflow soldering is close to the trend of competing products and the DSC curing onset is significantly reduced, its storage stability becomes poor and the open time is very short, which is not conducive to the actual sizing process operation.
[0054] Comparison of the data of Comparative Example 3 and Comparative Example 1 shows that if only the self-synthesized accelerator CJ-01 is used to prepare the formula, except for a slight decrease in the DSC curing peak onset and an increase in the high-temperature modulus before and after reflow soldering, the other performances are close to those of Comparative Example 1 and fail to reach the performance level of Competitor X. In addition, because the self-synthesized product is a powder solid with a large particle size and easy to agglomerate, direct use may affect the flow and filling performance.
[0055] From the comparison of the data of Comparative Example 4 and Comparative Example 1, it can be seen that if the independently synthesized accelerator CJ-01 and the main raw material EC331 in the controllable post-curing additive are used to prepare the formula, the DSC curing peak onset is significantly reduced, and the high-temperature modulus before and after reflow soldering is close to that of competitor X. However, like Comparative Example 2, the storage stability becomes poor and the open time is very short, which is not conducive to the actual sizing process operation. This shows that EC331 will be more active when used directly in this formula, which is not conducive to stability and operation time.
[0056] Examples 1 and 2 are mainly to verify the appropriate dosage of the independently prepared accelerator premix CP-01. Compared with Comparative Example 3, the performance is slightly different, but as mentioned above, after making the accelerator premix, the powder accelerator can be dispersed as much as possible, and it is more stable to use, and will not cause adverse effects on flow filling. Compared with the basic formula of Comparative Example 1, the DSC curing peak onset is reduced, and the high-temperature modulus before and after reflow soldering is significantly increased, approaching the level of competitor X. Since the accelerator CJ-01 in CP-01 is the product of the reaction of anhydride and imidazole, the basic activity is relatively low, especially when used in an amine system, and the premix is combined with alicyclic epoxy resin, it can finally continue to release part of the activity under high temperature conditions, which plays a role in improving the high-temperature modulus.
[0057] Examples 3 and 4 are mainly used to verify the appropriate amount of YP-01, an additive that can control the post-curing performance, which is prepared independently. It can be seen that the higher the amount of the additive that can control the post-curing performance, the higher the high-temperature modulus before and after reflow soldering, and the greater the rising ratio. Compared with Comparative Example 2, it can be clearly seen that when EC331 is used as a raw material to make YP-01 and then used in the formula, the DSC curing onset is reduced, and more importantly, the storage stability is significantly improved, and the open time is greatly extended, which is beneficial to the actual sizing process. The main reason for this phenomenon is that EC331 first undergoes a pre-crosslinking reaction with the epoxy resin, which greatly reduces the reactivity of EC331, and barbituric acid is used as an inhibitor to prevent it from over-reacting. However, some of the activity of EC331 and its alicyclic structure are still retained, which allows partial reactions to continue to occur under high temperature conditions and improve the high-temperature modulus.
[0058] Example 5 combines Examples 1-4 and innovatively uses the accelerator premix CP-01 together with the additive YP-01 that can control the post-curing performance. Compared with the test results of Examples 1-4 and Comparative Examples 1-4, it can be seen that after optimizing the dosage of CP-01 and YP-01, many properties are balanced after the two work synergistically in the formula. Compared with competitor X, the high-temperature modulus and growth ratio after reflow soldering have reached the level of competitor X, or even slightly higher; the room temperature storage stability and operating open time are also better than competitor X; the high-temperature pudding mold adhesion before and after UHast is also higher. This is because CP-01 and YP-01 both have a part of their activity released under high temperature conditions, and because the two have higher activity than other resins and curing agents in the formula, and there is a certain reactivity between the two, so the combined effect plays the role of the test performance, and ultimately enables it to achieve the purpose of passing the reliability test.
[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high reliability bottom filler suitable for large size chips, characterized in that: The raw materials include by weight: 25-35 parts of bisphenol F epoxy resin, 1-3 parts of bisphenol A epoxy resin, 0.5-2 parts of silicon-modified epoxy resin, 0.5-1.5 parts of black paste, 0.8-1.2 parts of coupling agent, 0.1-0.5 parts of flow aid, 50-55 parts of spherical filler, 10-15 parts of curing agent, 0.2-0.8 parts of accelerator premix and / or 0.5-1 parts of additives for controllable post-curing properties.
2. The high-reliability bottom filler for large-size chips according to claim 1, characterized in that: The raw materials for preparing the accelerator premix include accelerator.
3. The high-reliability bottom filler for large-size chips according to claim 2, characterized in that: The preparation method of the accelerator comprises the following steps: 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2-ethyl-4-methylimidazole and ethanol are added to a reaction container in sequence, the temperature is raised to 50-80°C, stirred for 6-10 hours, and then the reaction product is vacuum filtered and finally dried in an oven at 80-120°C for 2 hours to obtain a promoter.
4. The high-reliability bottom filler for large-size chips according to claim 3, characterized in that: The molar ratio of the 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride to 2-ethyl-4-methylimidazole is 1:1-3, and the ratio of the total moles of the 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride and 2-ethyl-4-methylimidazole to the moles of ethanol is 1:1-3.
5. The high-reliability bottom filler suitable for large-size chips according to any one of claims 2 to 4, characterized in that: The preparation method of the accelerator premix comprises the following steps: According to parts by weight, 25-35 parts of bisphenol A epoxy resin and 25-35 parts of alicyclic epoxy resin are mixed and stirred evenly, and then 35-45 parts of accelerator are added, stirred evenly, and then ground to obtain an accelerator premix.
6. The high-reliability bottom filler for large-size chips according to claim 1, characterized in that: The preparation method of the additive with controllable post-curing performance comprises the following steps: According to parts by weight, 70-80 parts of bisphenol F epoxy resin and 20-30 parts of alicyclic amine curing agent are heated to 40-60° C., mixed and stirred for 1-4 hours, and then 0.5-1 parts of barbituric acid are added, and the mixing and stirring is continued for 1-2 hours to obtain an additive with controllable post-curing performance.
7. The high-reliability bottom filler for large-size chips according to claim 1, characterized in that: The coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-aminopropyltrimethoxysilane.
8. The high-reliability bottom filler for large-size chips according to claim 1, characterized in that: The curing agent is at least one of maleic anhydride, benzoic anhydride, phthalic anhydride, succinic anhydride, 4,4'-diamino-3,3'-diethyldiphenylmethane, diethyltoluenediamine, diaminodiphenyl sulfone, m-aminomethylamine, benzyl dimethylamine trimer, and bisbenzyl amino ether.
9. A method for preparing a high-reliability bottom filler suitable for large-size chips as claimed in any one of claims 1 to 8, characterized in that: The steps include: Mix 25-35 parts of bisphenol F epoxy resin, 1-3 parts of bisphenol A epoxy resin, 0.5-2 parts of silicon-modified epoxy resin, 0.5-1.5 parts of black paste, 0.8-1.2 parts of coupling agent and 0.1-0.5 parts of flow aid for 1-4 hours; add 50-55 parts of spherical filler in 2-4 times, and continue to stir at a temperature range of 70-90°C for 6-10 hours; then cool to room temperature, first add 10-15 parts of curing agent, control the temperature at 25-30°C and stir for 0.5-2 hours; then add 0.2-0.8 parts of accelerator premix, control the temperature at 25-30°C and stir for 0.5-2 hours; finally add 0.5-1 part of an additive with controllable post-curing performance, control the temperature at 25-30°C and stir for 0.5-2 hours.
10. The method for preparing a high-reliability bottom filler suitable for large-size chips according to claim 9, characterized in that: The entire preparation process is carried out under vacuum conditions, and the vacuum degree is not less than -0.08Mpa.
Citation Information
Patent Citations
High-weather-resistant low-temperature thermosetting epoxy module adhesive and preparation method thereof
CN110591622A
Single-component epoxy resin packaging transparent adhesive tape and application thereof
CN112280509A
Single-component epoxy adhesive as well as preparation method and application thereof
CN116218442A
Low-temperature curing flip chip filling adhesive and preparation method thereof
CN116875252A
Epoxy underfill adhesive and preparation method thereof
CN117701213A